2009
DOI: 10.1016/j.neuron.2009.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Oscillations by Axonal Bursts in Inferior Olive Neurons

Abstract: SummaryInferior olive neurons regulate plasticity and timing in the cerebellar cortex via the climbing fiber pathway, but direct characterization of the output of this nucleus has remained elusive. We show that single somatic action potentials in olivary neurons are translated into a burst of axonal spikes. The number of spikes in the burst depends on the phase of subthreshold oscillations and, therefore, encodes the state of the olivary network. These bursts can be successfully transmitted to the cerebellar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
280
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(303 citation statements)
references
References 61 publications
20
280
1
Order By: Relevance
“…An alternative to the long-held error detection hypothesis is that the inferior olive is sensitive to the timing of sensory input. The intrinsic capacity of the olivocerebellar system to encode temporal information is supported by evidence from more recent electrophysiological studies demonstrating that stimulus timing is encoded relative to the phase of oscillations of the olivary neurons (10,11,14,15). In vitro experiments that used intracellular recording and voltage-sensitive dye imaging of inferior olive slices have shown that an extracellular stimulus "resets" the olivary neuronal oscillations and leads to synchronized firing of a large group of neurons in phase with the external stimulus (43,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative to the long-held error detection hypothesis is that the inferior olive is sensitive to the timing of sensory input. The intrinsic capacity of the olivocerebellar system to encode temporal information is supported by evidence from more recent electrophysiological studies demonstrating that stimulus timing is encoded relative to the phase of oscillations of the olivary neurons (10,11,14,15). In vitro experiments that used intracellular recording and voltage-sensitive dye imaging of inferior olive slices have shown that an extracellular stimulus "resets" the olivary neuronal oscillations and leads to synchronized firing of a large group of neurons in phase with the external stimulus (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…However, implicit timing or timing without awareness has been difficult to characterize in experimental settings, especially in animal studies, and its neural correlates remain poorly understood (5). One system that has long been implicated in event timing is the olivocerebellar system, which originates exclusively in the inferior olive (6)(7)(8)(9)(10)(11)(12). Whether the olivocerebellar system mediates timing without awareness has not been demonstrated directly to our knowledge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of techniques allowing loose-patch (22,70,116,362,422) or whole cell recording (291,355,463,489,561) from single axons of mammalian neurons, together with the use of voltage-sensitive dyes (196,396,397) or sodium imaging (46,193,290), provide useful means to precisely determine the spike initiation zone. These recordings have revealed that sodium spikes usually occur in the axon before those in the soma (Fig.…”
Section: Initiation In the Axonmentioning
confidence: 99%
“…For a long time, climbing fiber input to a Purkinje cell was considered to be all-or-none. However, recent studies show that the number of spikes in the brief high-frequency burst of climbing fiber is tightly regulated De Gruijl et al 2012;Maruta et al 2007;Mathy et al 2009). These studies suggest that climbing fibers actually convey graded signals by changing the number of spikes in their high-frequency bursts, and such graded signals are proposed to encode more flexible instructive signals for Purkinje cells (Najafi and Medina 2013).…”
Section: Discussionmentioning
confidence: 99%